Entrepreneurship-driven Migratory Behaviour Among the Tea Estate Workers in West Bengal: An Exploratory Study - Debarshi Roy (Vikalpa)
The tea estate workers of West Bengal have been victims of colonial oppression for generations. The experiences of the workers with oppressive business cultures have resulted in unique complexities within their behaviour. Migratory entrepreneurship will augur socio-economic growth among the tea estate communities while enhancing the efficiency of the tea estates. The present study explores the behavioural dimensions of migratory entrepreneurship among the tea estate workers of Bengal through a multi-dimensional approach which includes a discussion on the historical, socio-economic perspective, a field study on perceptions of migratory entrepreneurship among the garden community and a subsequent analysis of the results.